Heat Shock Protein 90 kDa (Hsp90) Has a Second Functional Interaction Site with the Mitochondrial Import Receptor Tom70 - Zanphorlin, Leticia M.; Lima, Tatiani B.; Wong, Michael J.; Balbuena, Tiago S. [UNESP]; Minetti, Conceicao A. S. A.; Remeta, David P.; Young, Jason C.; Barbosa, Leandro R. S.; Gozzo, Fabio C.; Ramos, Carlos H. I. (Amer Soc Biochemistry Molecular Biology Inc, 2016)
To accomplish its crucial role, mitochondria require proteins that are produced in the cytosol, delivered by cytosolic Hsp90, and translocated to its interior by the translocase outer membrane (TOM) complex. Hsp90 is a dimeric molecular chaperone and its function is modulated by its interaction with a large variety of co-chaperones expressed within the cell. An important family of co-chaperones is characterized by the presence of one TPR (tetratricopeptide repeat) domain, which binds to the C-terminal MEEVD motif of Hsp90. These include Tom70, an important component of the TOM complex. Despite a wealth of studies conducted on the relevance of Tom 70 center dot Hsp90 complex formation, there is a dearth of information regarding the exact molecular mode of interaction. To help fill this void, we have employed a combined experimental strategy consisting of cross-linking/mass spectrometry to investigate binding of the C-terminal Hsp90 domain to the cytosolic domain of Tom70. This approach has identified a novel region of contact between C-Hsp90 and Tom70, a finding that is confirmed by probing the corresponding peptides derived from cross-linking experiments via isothermal titration calorimetry and mitochondrial import assays. The data generated in this study are combined to input constraints for a molecular model of the Hsp90/Tom70 interaction, which has been validated by small angle x-ray scattering, hydrogen/deuterium exchange, and mass spectrometry. The resultant model suggests that only one of the MEEVD motifs within dimeric Hsp90 contacts Tom70. Collectively, our findings provide significant insight on the mechanisms by which preproteins interact with Hsp90 and are translocated via Tom70 to the mitochondria.